Real Time Monitoring for Smart Water Quality - Hamzah, Shipuan Anuar; Devarajah, Kishen Kumaar (Evolution in Electrical and Electronic Engineering, 2024)
The main purpose of this project is to develop a real time water quality monitoring system to test the water in the lakes around UTHM. Presence of contaminants such as chemicals, heavy metals and microorganisms in the water can be harmful to aquatic life and environment. By developing this system, it will help to monitor the water quality in the lakes around UTHM. The data from the system can be monitored in the Blynk platform as well. Node MCU ESP32 Microcontroller board was used as the primary computing element to control the hardware in this project. Three sensors were used to monitor the water quality which turbidity sensor, temperature sensor and pH sensor and the data from the sensors had been successfully sent to the Blynk platform with the aid of the Wi-Fi. The system was tested in three lakes around UTHM which is lake Infront FKEE, lake Infront FPTP and also Taman Universiti Lake and within 3 days observation, the system has shown the data of the monitoring system which was tested in these three lakes. This system has achieved its objective by successfully measured the water quality in the three lakes and also the system was verified as its working accurately.